POPULATION STRUCTURE AND MORPHOMETRY OF HORSESHOE CRAB Carcinoscorpius rotundicauda, Latreille 1802 IN KAMPUNG GISI COASTAL AREA OF BINTAN BAY OF RIAU ISLANDS PROVINCE - Rika Anggraini; Dietriech G. Bengen; Nyoman Metta N. Natih (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Horseshoe crab, Carcinoscorpius rotundicauda is frequently found in the coastal zone of Bintan Bay of Riau Islands Province. The study was conducted from August to September 2016 in coastal area of Kampung Gisi, Bintan bay. The aims of the study were to analyse the population structure and morphometric characters of horseshoe crab and its relation to the coastal environmental characteristics. Sampling of horseshoe crab was taken using belt transect method, and coastal environmental parameters were measured in-situ. The results show that b values of length-weight relationship were found to be 3.3 (male) and 2.6 (female) respectively. Furthermore, the growth pattern of males were positive allometric, and females were negative allometric. Horseshoe crab are closely related to sandy mudflats sediment, brackish water salinity and mangrove habitat distribution. Keywords: horseshoe crab, population structure, morphometry, environmental characteristics, Bintan Bay